Easy money cryptocurrency, casino capitalism, and the golden age of fraud - McKenzie, Benjamin 1978-; Silverman, Jacob (Abrams Press, 2023)
"A famous actor and an experienced journalist present an entertaining debunking of cryptocurrency, from its initial promise of taking power from banks while providing quick riches to its current spectacular crash"--
Keywords: Virtuelle Währung; Kapitalanlage; Kapitalanlagebetrug; Betrug; USA; Cryptocurrencies; Fraud; White collar crimes; Investments; Actors; BUSINESS & ECONOMICS / Investments & Securities; TRUE CRIME / Con Artists, Hoaxes & Deceptions; TRUE CRIME / White Collar Crime; Anecdotes